Is circumferential urethral mobilization an overdo? A prospective outcome analysis of dorsal onlay and dorso - lateral onlay BMGU for anterior urethral strictures - Prakash,Gaurav (2018)
ABSTRACT Introduction For dorsal onlay graft placement, unilateral urethral mobilization is less invasive than standard circumferential urethral mobilization. Apart from success in terms of patency of urethra, other issues like sexual function, overall quality of life and patient satisfaction remain important issues while comparing outcomes of urethroplasty. Aim To prospectively compare the objective as well as subjective outcomes of two approaches. Materials and Methods Between July 2011 and January 2015, 136 adult males having anterior urethral stricture with urethral lumen ≥ 6 Fr. were prospectively assigned between two groups by alternate randomization. Operative time, complications, success rate (no obstructive symptoms, no need of any postoperative intervention, Q max > 15mL/sec), sexual functions (using Brief Male Sexual Function Inventory) were compared. Results Baseline parameters were similar in both groups (68 in each group). Overall success rate was similar in both groups (89 % and 91 % respectively). Improvement in total LUTS scores was similar in groups. Changes in overall health status (VAS and EQ 5D) was equal in both groups. Erectile function score was significantly decreased in DO than DL group while ejaculatory function and sexual desire remained stable after urethroplasty in both groups. Conclusions In anterior urethral stricture buccal mucosa graft provides satisfactory results as onlay technique. No technique whether dorsolateral and dorsal techniques is superior to other. Dorsolateral technique needs minimal urethral mobilization and should be preferred whenever feasible.